The Effect of Environmental Costs, Environmental Disclosure, Environmental Performance, and Profitability on Firm Value - Fristianti, Ega; Novi, Novi; Komara, Acep (Journal Research of Social Science, Economics, and Management, 2024)
A company's worth is a key metric for maintaining its competitiveness in the face of fierce industry rivalry. The purpose of this study is to examine how firm value is impacted by environmental costs, environmental disclosure, environmental performance, and profitability. The study was conducted on companies listed on the Indonesia Stock Exchange from 2018 to 2022, employing purposive sampling to select 10 companies. Panel data regression analysis using Eviews 12 software was employed to test the hypotheses. The findings suggest that Environmental Costs do not influence Firm Value, whereas Environmental Disclosure and Environmental Performance do impact Firm Value. However, Profitability was found to have no effect on Firm Value. Based on the results of statistical tests and based on the discussion described in the previous chapter, the conclusions of this study are as follows: Environmental Cost does not affect firm value in industrial and chemical sector companies. The nature of environmental accounting disclosure is still voluntary.